Effects of Cryogenic Treatment after Annealing of Ti-6Al-4V Alloy Sheet on Its Formability at Room Temperature - Zhiqing Hu; Huihui Zheng; Guojun Liu; Hongwei Wu (Metals, 2018)
In this article, the effects of cryogenic treatment after annealing on the formability of Ti-6Al-4V alloy sheet were experimentally studied. The Ti-6Al-4V titanium alloy was treated by cryogenic treatment after annealing (ACT). Tensile tests were carried out using a universal machine at room temperature. The microstructure evolution of Ti-6Al-4V subjected to ACT was also investigated using an optical microscope (OM). Both the shearing performance and drawing formability were analyzed by punch shearing tests and deep drawing tests, respectively. Results showed that after ACT, the tendency of the β phase can be apparently changing into stable β’ and α’ phases. The elastic modulus is lower than that of the untreated material. It was found that both the yield strength and tensile strength are declined slightly, whereas the ductility is increased significantly. The shear strength in punch shearing is decreased at room temperature and cryogenic temperature. The ratio of smooth zone on the section after ACT3 is much larger than the others. The rollover diameters are not obviously greater than those of the untreated. Additionally, the height of the burr shows a decreasing trend after ACT. During deep drawing, drawing depth is deeper than that of the untreated material, the drawing load after ACT is reduced, and the decreasing tendency of the drawing load slows down. It is noted that the micro-cracks occur at the bottom of the sample.